PENARIKAN BARANG JAMINAN PADA PRODUK PEMBIAYAAN GRIYA DI BANK SYARIAH INDONESIA (BSI) DALAM TINJAUAN KHES - Ayu Karina; Sukardi Sukardi; Nanda Himmatul Ulya (Al-Aqad, 2023)
This study aims to find out the activities of leasing coconut plantations in Teluk Nangka Village, Kubu District, in this case, leasing is carried out with two different contract systems. This study uses a qualitative approach. The primary data source is in the form of interviews from musta'jir (tenants) and mu'ajir (renters). Secondary data comes from various parties such as the results of journals, articles, and theses. The study results show that: 1) In the practice of leasing contracts for coconut plantations in Teluk Nangka Village, two systems are used, namely on a monthly and annual basis. Monthly system by paying rent every month and the object of rent in the beneficiary is only the garden. Meanwhile, the annual system is a one-time payment, usually made in cash or a certain number of days with a bonus of 1 month. Thus, the annual rental period is 13 months. The contract agreement is made orally and has never used a written contract. Pricing is determined based on the condition of the garden, area, and unit of time to be rented and agreed upon at the beginning of the contract. Maintenance of the coconut plantation is the responsibility of the musta'jir i. The end of the lease for coconut plantations in Teluk Nangka Village because the lease period in the agreement has ended; 2) Whereas the practice of leasing contracts contained in the Compilation of Sharia Economic Law (KHES) in Chapter XI Articles 295-320 supports the leasing contract for coconut plantations in Teluk Nangka Village. It is only that the agreement between the two parties must have a clear statement so that the transaction is full of honesty and fairness.